(untitled) (Journal of Computational Mathematics, 1985)
In this article the high order approximation of the one-way wave equations are discussed. The approximate dispersion relations are expressed in explicit form of sums of simple fractions. By introducing new functions, the high order approximations of the one-way wave equations are put into the form of systems of lower order equations. The initial-boundary value problem of these systems which corresponds to the migration problem in seismic prospecting is discussed. The energy estimates for their solutions are obtained.